PEMIKIRAN POLITIK KHALID MUHAMMAD KHALID - Musyafaah, Nur Lailatul (Jurnal Review Politik, 2015)
This article discusses the Political Thought that Khalid Muhammad Khalid experience the duality of political thought. In the 1950s, when he wrote "Min Huna Nabda '" he believes religion is not a state, it must be a separation between religion and state. Based on his view that there should be a purification of the religion (Islam) from the clergy, upholding the concept of sosialism in public life, keep the desire to have a religious government, and provide political freedom for women. However, in the 1980s Khalid wrote the book "al-Daulah fi al-Islam". In his book, he revised the previous view on the separation of religion and state, and said that religion also set the state. Thus, Islam is religion and state. His thinking is influenced by political and sosial conditions of Egypt at that time, and its proximity to the Muslim Brotherhood. Dualism of Islamic political thought Khalid Muhammad Khalid is a natural thing in the context of thinking.